STRENGTHENING SOCIAL SUPPORT FOR DRUG CASE INMATES IN PRISONS THROUGH COUNSELING AND CHARACTER DEVELOPMENT PROGRAMS: STRENGTHENING SOCIAL SUPPORT FOR DRUG CASE INMATES IN PRISONS THROUGH COUNSELING AND CHARACTER DEVELOPMENT PROGRAMS - Hariani, Wita; Yohanes Susanto; Kasman (Bengkulu Institute, 2025)
The high number of drug convicts in correctional institutions (prisons) causes various problems, including low social support which has an impact on psychological well-being and the risk of recidivism. This community service program aims to strengthen social support for inmates through the implementation of counseling and character building. The activities were carried out at the Class III Penitentiary in Pagar Alam City with a participatory approach. The methods used included individual counseling, group therapy, and character building based on spirituality and nationalism. The results of the activities showed an increase in self-esteem, self-awareness, and social adaptation abilities of inmates. However, challenges such as limited human resources and lack of family support are still obstacles to optimal program implementation.